Respuesta :

Answer: 5

===============================================

Explanation:

Look at the entries of each table when x = 2

For p(x), we have p(x) = 3 when x = 2

For q(x), we have q(x) = -2 when x = 2

Both of these are the second row of each table.

---------

Subtract these function output values mentioned

3 minus -2 = 3 - (-2) = 3 + 2 = 5

Note how the two negatives cancel to make a positive. Subtracting a negative is the same as adding.

The table given can be computed as follows:

x        p(x)        ║        x           q(x)

4          -1         ║        4             1

2          3          ║        2           -2

-3         2          ║       -3            5

From the given information, the objective is to find (p - q;  when (x) = 2

  • For p(x); we have p(x) = 3
  • For q(x); we have q(x) = -2

To find (p -q);

= (3 - ( -2))               ∵ (-) × (-) = +

= (3 + 2)

= 5

Therefore, we can conclude that the value of (p-q) when x = 2 is 5

Learn more about completing the values on a table here:

https://brainly.com/question/8629807?referrer=searchResults

ACCESS MORE